Perceived Risk, Structural Assurance and Trust in Mobile Payments - Sahli Sassi, Afef; Hammami, Hanéne; Ben Lallouna Hafsia, Hajer (Journal of Telecommunications and the Digital Economy, 2022)
Mobile technologies have emerged as a new business phenomenon as a result of the increasing popularity of mobile devices and the proliferation of mobile technologies. A number of marketing research studies have focused on the identification of the background and consequences of mobile commerce, thus enabling m-commerce service providers to design appropriate marketing strategies. This paper’s major contributions are the importance of trust in adopting mobile payments under the influence of perceived risk and structural assurance, as well as the identification of business-related factors that affect mobile trust. A quantitative study was carried out, with 175 valid auto-administered questionnaires collected and analysed using structural equations modelling. The analysis results indicate the positive effect of perceived risk and structural assurance in mobile trust on mobile payment adoption intention. It is important to raise managers’ awareness of preserving the security of services in order to develop mobile trust. Also, to reduce the perceived risk associated with mobile financial transactions, managers need to provide basic insurance for customers in order to defend their transactions in the event of fraud or a particular problem.